2010
DOI: 10.1093/eurjhf/hfq048
|View full text |Cite
|
Sign up to set email alerts
|

Implantable defibrillator therapy for ventricular tachyarrhythmia in left ventricular assist device patients

Abstract: AimsVentricular arrhythmias (VA) occur frequently after permanent left ventricular assist device (LVAD) implantation in end stage heart failure. Left ventricular assist device patients require rhythm control in contrast to patients with biventricular support. However, the rationale for implantable cardioverter-defibrillator (ICD) utilization in LVAD patients remains unclear. This study investigated the safety and efficacy of primary prevention ICD therapy and the rate of appropriate ICD interventions in LVAD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 24 publications
7
83
1
2
Order By: Relevance
“…Survival, transplantation rates, and hospitalizations were similar during follow‐up. Mortality rates noted in our study are comparable to randomized trials of CF‐LVAD as well as prior studies evaluating ICD therapies in LVADs 1, 2, 6, 19, 20…”
Section: Discussionsupporting
confidence: 87%
“…Survival, transplantation rates, and hospitalizations were similar during follow‐up. Mortality rates noted in our study are comparable to randomized trials of CF‐LVAD as well as prior studies evaluating ICD therapies in LVADs 1, 2, 6, 19, 20…”
Section: Discussionsupporting
confidence: 87%
“…As mentioned, ventricular arrhythmias are among the most common, occurring in 20-50 % of supported patients. [4][5][6][7][8][9] While the greatest risk tends to be in the first month following device implantation, 8 there is a growing body of evidence to suggest that later arrhythmic events are still important. In addition, recurrence following an initial episode is common, 9 making care of affected patients an ongoing and laborious challenge.…”
Section: Epidemiology and Aetiology Of Ventricular Arrhythmias Duringmentioning
confidence: 99%
“…Some investigators have demonstrated greater rates of arrhythmic events among patients with ischaemic heart disease, 10,11 while others have suggested that non-ischaemic patients are at higher risk. 8 The absence of postoperative beta-blocker therapy, 12 prolongation of the baseline QT interval, 13 and deranged serum electrolytes have all been touted as risk factors as well, 11 but none of these have been well validated. In fact, only the presence of pre-implantation ventricular tachycardia (VT) has been repeatedly shown to be a powerful predictor of future episodes of VT after LVAD.…”
Section: Epidemiology and Aetiology Of Ventricular Arrhythmias Duringmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 ventricular arrhythmias Ventricular arrhythmias affect at least one third of patients treated with long-term VAD support for advanced HF. 56 Several factors affect the likelihood of ventricular arrhythmias occurring during VAD support. Of these, the most consistently observed risk factor is a history of ventricular arrhythmias prior to initiation of VAD support.…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%